Finite element analysis of warpage in laminated aluminium alloy plates for machining of primary aeronautic parts - Reis, A. C.; Menezes, M. A. [UNESP]; Filho, L. A. Moreira (AIP Publishing, 2007)
The aim of this paper consists in presenting a method of simulating the warpage in 7xxx series aluminium alloy plates. To perform this simulation finite element software MSC.Patran and MSC.Marc were used. Another result of this analysis will be the influence on material residual stresses induced on the raw material during the rolling process upon the warpage of primary aeronautic parts, fabricated through machining (milling) at Embraer. The method used to determinate the aluminium plate residual stress was Layer Removal Test. The numerical algorithm Modified Flavenot Method was used to convert layer removal and beam deflection in stress level. With such information about the level and profile of residual stresses become possible, during the step that anticipate the manufacturing to incorporate these values in the finite-element approach for modelling warpage parts. Based on that warpage parameter surely the products are manufactured with low relative vulnerability propitiating competitiveness and price. © 2007 American Institute of Physics.
Keywords: Aluminium alloy plates; And MSC.marc; Finite element modelling; Milling; Residual stress; Warpage